The role of plateletcrit and neutrophil lymphocyte ratio in showing the clinical severity of the disease in patients with chronic venous insufficiency - Engin, Mesut; Tugrul Goncu, Mehmet (Annals of Medical Research, 2021)
Aim: Chronic venous insufficiency (CVI) is a common disease and affects approximately 40% of the population. In this study, we aimed to investigate the relationship of neutrophil to lymphocyte ratio (NLR) and plateletcrit (PCT) values with the clinical severity of the disease in patients diagnosed with CVI.Material and Methods: The patients hospitalized to our clinic for treatment with the diagnosis of chronic venous insufficiency between August 2014 and August 2019 were included in the study retrospectively. Patients were divided into two groups as Group 1 including patients with stage C1, C2, C3 disease and Group 2 including patients with stage C4, C5, C6 disease according to the clinical evaluation in CEAP staging.Results: There were 119 patients in Group 1 and their median age was 35 (18- 66) years. There were 55 patients in Group 2 and their median age was 44 (19- 65) years. In multivariate logistic regression analysis, the presence of concomitant perforator vein incompetence (Odds ratio(OR): 1.527, CI 95%: 1.481-2.846 p = 0.019), presence of concomitant deep venous insufficiency (OR: 1.978 CI 95%: 1.250-2.979 p = 0.020), NLR (OR: 3.244, CI 95%: 1.384-4.825 p0.001) and PCT (OR: 5.354 CI 95%: 2.935-8.586, p = 0.001) values were found to be independent predictors in showing the clinical severity of venous disease.Conclusions: We determined that the severity of the clinical condition could be predicted by NLR and PCT values in patients with superficial venous insufficiency, the most common insufficiency in the population.
Keywords: Chronic venous insufficiency; inflammation; neutrophil to lymphocyte ratio; plateletcrit; platelets